Aplicación de Contabilidad Comercial y análisis de la Nic 1 en “Minimarket Amadita” del Cantón Santa Cruz, Provincia de Galápagos, período mayo – junio 2016 - Villavicencio Taco, Mario Patricio (2017)
This present thesis was developed with the aim of raising awareness of the economic results of the accounting cycle, in addition to the appropriate procedure that this business must use for the control of its commercial activity. With the application of commercial accounting and analysis of financial statements for proper presentation, it was to determine the economic performance of the studied period, after the lifting of the initial inventory, journaling book, application of internal documents such as purchase books, sales, depreciation, payroll, kardex by the weighted average method, bank reconciliation, among other instruments; whose records demonstrate the accuracy of the information until economic performance through balance sheets; considering the international accounting standards IAS 1; it referred to the presentation of financial statements. Finally presents the conclusions and recommendations related to commercial accounting applied on the basis of the accounting rules and tax whose results were disclosed in a timely manner to its owner.